Determination of Crop Coefficient of Tea - Sikka, Alok K; Sahoo, D C; Madhu, M; Selvi, V (Journal of Agricultural Engineering, 2009)
Crop coefficient of tea was determined based on evapo-transpiration data (1996-2001) using weighing type lysimeter. Weekly reference crop evapotranspiration (ETo) was worked out for the same period by FAO Penman–Monteith (FAO 56-PM) equation using daily meteorological data. This ETo, along with observed crop evapotranspiration (ETc), was used to determine the crop coefficient (Kc). The average Kc values for the initial season, mid season and late season were found to be 0.80, 1.31 and 0.71, respectively with the corresponding average ETc of 2.77, 3.31 and 2.27 mm/day, respectively.